The Impact of Strategic Intelligence on Organizational Excellence: A Field Study in Yemeni Banks in the Capital Municipality of Sana'a - Gamal Dirhim Ahmed Zaid; Mohammed Abdullah Al-Sabahi (University of Science and Technology, Sana’a, Yemen, 2026)
This study aimed to identify the impact of strategic intelligence, represented by its dimensions (foresight, systems thinking, future vision, and partnership), on organizational excellence represented by its dimensions (leadership excellence, operational excellence, service excellence, and human resources excellence) in Yemeni banks located in the Capital Municipality of Sana'a. The study adopted a descriptive-analytical approach and used a questionnaire as a tool for data collection from administrative leaders in 13 banks, with a sample size of 295 respondents. Data were analyzed using Structural Equation Modeling (SEM) through the SmartPLS software, in addition to statistical analysis via SPSS. The results indicated a positive statistically significant impact of strategic intelligence on organizational excellence. All dimensions of strategic intelligence showed a significant positive impact on organizational excellence, with the partnership dimension having the greatest influence, followed by future vision, foresight, and then systems thinking. The study recommends enhancing the application of strategic intelligence, particularly systems thinking, updating foresight and future vision tools, and expanding strategic partnerships to support the achievement of sustainable organizational excellence.